PERANCANGAN WEBSITE SEBAGAI MEDIA PUBLIKASI DESA KEBON IX KEC. SUNGAI GELAM KAB. MUARO JAMBI: PHP, MYSQL,bootstrap css,system, web - Susanto, Darex (JURNAL AKADEMIKA, 2018)
Website is an information media that offers various facilities in presenting information. Speed and comfort are positive values for internet. Kebon IX village is one of the villages located in Sungai Gelam sub-district, Muaro Jambi district which does not have a website to provide information to the wider community or villagers. Kebon IX Village website design which can later be useful for all parties. Making this website uses css bootstrap and PHP MySQL as the database. In order for this website to be able to provide information quickly and accurately.